Human Capital Development and Economic Growth: A Literature Review on Information Technology Investment, Education, Skills, and Productive Labour - Ferly Agustina Sairmaly (Jurnal Minfo Polgan, 2023)
A country's economic growth is influenced by various factors, including human resource development. High-quality and productive human resources are the main key in promoting sustainable economic growth. Therefore, this study aims to conduct a literature review on education investment, information technology, skills, and productive labour in the context of human capital development and economic growth. The focus of this study is primarily qualitative. Methods for gathering data include paying close attention to detail while viewing and recording data, and then using analytical techniques such as data reduction, visualisation, and inference to draw conclusions. The study arrives at the conclusion that human capital development through investments in education, information technology, skills, and productive labour plays a crucial role in a country's economic growth. For example, investment in quality education provides individuals with knowledge and skills, expands employment opportunities, and increases people's purchasing power.